Intubation outside of the operating room: new challenges and opportunities in COVID-19 era - Lee, Delice Weishan (Curr Opin Anaesthesiol, 2020)
PURPOSE OF REVIEW: Airway management in patients outside the operating room is associated with increased difficulties and risks, and the setting of the COVID-19 global pandemic adds another layer of complexity. Therefore, endotracheal intubation (ETT) of a patient who is presumptive COVID-19 or COVID-19 positive presents an additional challenge to an anesthesiologist. The aim of this review is to summarize the important principles of airway management outside of the operating room during the COVID-19 pandemic. RECENT FINDINGS: Several professional societies have formulated guidelines on airway management COVID-19 suspect and proven patients. Additionally, anesthesiologists working in hospitals treating many infected patients have developed specialized teams responsible for airway management outside the operating room. These documents and protocols focus on the importance of wearing personal protective equipment and the skills of the providers responsible for securing the airway. Staff safety is always a priority when performing ETT outside operating room. SUMMARY: The COVID-19 pandemic redefined the management of patients requiring aerosol generating procedures (droplet and airborne precautions). ETT is one of them and anesthesiologists are experts in performing airway management. Although the operating room is a highly controlled environment, airway management outside of this setting is not always the easiest task.